Homogenization and impoverishment of taxonomic and functional diversity of ants in Eucalyptus plantations - Martello, Felipe [UNESP]; De Bello, Francesco; De Castro Morini, Maria Santina; Silva, Rogério R.; De Souza-Campana, Débora Rodriges; Ribeiro, Milton Cezar [UNESP]; Carmona, Carlos P. (Springer Nature, 2018)
Despite its negative impacts on the environment and biodiversity, tree plantations can contribute to biodiversity conservation in fragmented landscapes, as they harbor many native species. In this study, we investigated the impact of Eucalyptus plantations on the taxonomic and functional diversity of ant communities, comparing ant communities sampled in managed and unmanaged (abandoned for 28 years) Eucalyptus plantations, and native Atlantic rain forests. Eucalyptus plantations, both managed and unmanaged, reduced the functional diversity and increased the similarity between ant communities leading to functional homogenization. While communities in managed plantations had the lowest values of both taxonomic and functional ant diversities, ant communities from unmanaged plantations had similar values of species richness, functional redundancy and Rao's Q compared to ant communities from forest patches (although functional richness was lower). In addition, communities in unmanaged Eucalyptus plantations were taxonomically and functionally more similar to communities located in managed plantations, indicating that Eucalyptus plantations have a severe long-term impact on ant communities. These results indicate that natural regeneration may mitigate the impact of Eucalyptus management, particularly regarding the functional structure of the community (α diversity), although it does not attenuate the effects of long term homogenization in community composition (β diversity).